Laparoscopic Repair of Peptic Ulcer Perforation - Our Initial Experience (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background: Laparoscopic repair of perforated peptic ulcer was reported in 1990 but has not gained wide acceptance. The aim of this study was to evaluate the safety and efficacy of laparoscopic repair in routine clinical practice.Methods: This was a prospective analysis of 30 patients who underwent laparoscopic repair of a perforated peptic ulcer between July 2009 and June2010.Results: Thirty patients of mean age 45 (range 25-52) years had perforated ulcer diagnosed by clinical examination and x-ray abdomen and confirmed by laparoscopy. 28 was duodenal ulcer perforation and rest 2 was gastric ulcer perforation. Only 3 patients required conversion to laparotomy out of them 2 were DU perforation and one was gastric ulcer perforation. Mean operation time was 75 (range 75-150) minutes. Mean postoperative hospital stay was 6 (5-10) days. Postoperative convalescences were good. There was no operation related complication but one patient needs transfer to ICU for delayed recovery and the patient eventually recovered well. Post-operative leakage occurred in one patient and that was treated by laparotomy. One of 3 conversion cases developed wound infection but wound related complications in laparoscopic cases were very negligibe.Conclusion: Laparoscopic repair is a safe and effective procedure for repair of perforated peptic ulcer.DOI: http://dx.doi.org/10.3329/jpsb.v1i2.19535